(untitled) (The International Journal for Scientific Research, 2024)
The study titled aimed to evaluate the knowledge, training, and practices of dental assistants concerning infection control standards in healthcare. Utilizing a structured questionnaire distributed via Google Forms, data were collected from 48 participants and analyzed using SPSS software. The results indicated varied levels of familiarity with infection control guidelines, with 54.2% of respondents expressing confidence in applying infection control measures. Training was a pivotal factor, as 47.9% reported occasional training and 37.5% received regular sessions, highlighting its role in fostering safer healthcare environments. Challenges in adhering to infection control practices were prevalent, with frequent and occasional difficulties reported by 56.3% of participants. Areas requiring further improvement included sterilization procedures (31.3%) and environmental cleaning (25%). The study emphasized the importance of continuous education, workplace support, and updates on infection control protocols to enhance compliance and awareness. Recommendations included implementing more frequent and comprehensive training sessions, introducing modern technological solutions, and promoting regular reviews of infection control policies.